2018
DOI: 10.20546/ijcmas.2018.710.359
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Distribution of Russula in India with Reference to Central Indian species

Abstract: The genus is represented by about 130 taxa from India (Das et al., 2014). North-western subtropical and temperate forests of Himalayan region of Uttarakhand state are represented most Russula species. There is a large gap that exists with respect to knowledge diversity of macro-fungi in India. For proper planning and management of forests and the conservation of their biodiversity, characterization, systematics and ecology of these macro-fungi is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Tedersoo and Nara (2010) also revealed that Russula-Lactarius lineages were relatively more diverse in tropical than temperate forests. Diverse Russulaceae fungi have also been obtained in tropical forests, in Peninsular Malaysia (Lee et al 2002), in India (Verma et al 2018), in West Africa (Bâ et al 2012), in Thailand (Phosri et al 2012), and in Malaysia (Essene et al 2017;Peay et al 2010). However, 15 taxa of Russula could not be identified at the species level in this study because their morphological features differed from the described species.…”
Section: Diversity and Community Of Ecm Fungi In Dipterocarpus Alatusmentioning
confidence: 99%
“…Tedersoo and Nara (2010) also revealed that Russula-Lactarius lineages were relatively more diverse in tropical than temperate forests. Diverse Russulaceae fungi have also been obtained in tropical forests, in Peninsular Malaysia (Lee et al 2002), in India (Verma et al 2018), in West Africa (Bâ et al 2012), in Thailand (Phosri et al 2012), and in Malaysia (Essene et al 2017;Peay et al 2010). However, 15 taxa of Russula could not be identified at the species level in this study because their morphological features differed from the described species.…”
Section: Diversity and Community Of Ecm Fungi In Dipterocarpus Alatusmentioning
confidence: 99%
“…in India. Ghosh A. et al 2016Ghosh A. et al , 2019Ghosh A. et al , 2020Verma et al 2018Verma et al , 2019Yuan et al 2020) but were very often identified based on overall similarity with their European and North American counterparts and without much critical comparative assessment of detailed macro-and, particularly, micromorphology (Pradhan et al 2012macro-and, particularly, micromorphology (Pradhan et al , 2013Ganguly et al 2021). Unfortunately, in-depth taxonomic studies of these Sal-associated Russula species have not yet been undertaken in India, although a only five Russula species were reported from Sal forest (particularly from the state of West Bengal) combining morphological study and phylogenetic inferences (Dutta et al 2015;Khatua et al 2015Khatua et al , 2017Khatua et al , 2021Yuan et al 2020).…”
Section: Introductionmentioning
confidence: 99%